Creation and Evaluation of a Polyurethane/Carbon/Zinc Oxide Film Composite for Use as a Coating Material - Kurniawan, Ova; Soegijono, Bambang (Universitas Negeri Jakarta, 2025)
The material used as a coating must have unique characteristics. A frequently used coating material is polyurethane. Even though Polyurethane has been widely used as a coating material, it has limitations in thermal resistance. Incorporating fillers such as carbon and ZnO can improve its thermal, dielectric, and corrosion-resistant properties. Composite films of polyurethane with carbon, ZnO, and a mixture of both were prepared. Characterizations included FTIR, TGA, DSC, XRD, dielectric testing, salt spray, water vapor permeability, hydrophobicity, and adhesion tests. FTIR confirmed the presence of functional groups from the fillers. TGA and DSC showed improved thermal stability, particularly in carbon-filled composites. Salt spray and permeability tests indicated enhanced corrosion resistance in ZnO-filled samples, while dielectric properties improved with carbon addition. Hydrophobicity and adhesion tests met coating material criteria. Among all variants, the polyurethane/carbon composite demonstrated the most favorable combination of thermal, dielectric, and surface properties, making it the most suitable for protective coating applications.